Soccer players have a better standing balance in nondominant one-legged stance - Rosario Barone; Filippo Macaluso; Marcello Traina; et al (Dove Medical Press, 2010)
Rosario Barone1, Filippo Macaluso2, Marcello Traina3,4, Vincenza Leonardi4,5, Felicia Farina1, Valentina Di Felice11Human Anatomy Section 'E. Luna', BioNeC, University of Palermo, Palermo, Italy; 2Department of Physiological Science, Stellenbosch University, Stellenbosch, South Africa; 3Department of Internal Medicine, Cardiovascular and Renal Diseases, 4Methods and Didactics of Motory Activities, DISMOT, 5Department of General Surgery, Emergency and Organ Transplants (GENURTO), University of Palermo, Palermo, Italy  Rosario Barone and Filippo Macaluso contributed equally to the workAbstract: The purpose of this study was to analyze the differences in standing balance during dominant and nondominant one-legged stance among athletes of different sports and sedentary subjects. The right-footed subjects of four groups (sedentary, n = 20; soccer, n = 20; basketball, n = 20; windsurfer n = 20) underwent 5-sec unipedal (left and right foot) stabilometric analysis with open eyes and closed eyes to measure center of pressure (COP) sway path and COP velocity (mean value, anteroposterior, and laterolateral in millimeters per second). The soccer group showed better standing balance on the left leg than the sedentary group (P < 0.05). No other significant differences were observed within and amongst groups. The soccer players have a better standing balance on the nondominant leg because of soccer activity.Keywords: body sway, bipedal stance, center of pressure, sport practice